RANCANG BANGUN ALAT PENAHAN MEDIA KONTRAS PADA PEMERIKSAAN COLON IN LOOP - Hardiyanti Putri Habiba; Eunike Rivena Natalia; Maulana Herbayu Aji; Muhammad Dzaky Irawan (Poltekkes Kemenkes Semarang, 2018)
ABSTRACTBackground: Colon in loop is a radiological examination to observe the intestinal organs using contrast media. Based on observation, examination of colon in the loop is more often done in mature patients. While in elderly patients occurs incontinence alvi that the anus function does not work well, so that when examined colon in the loop, the contrast media that was injected is go out of the intestine before the colon was photographed. It is intended on the results of the radiograph so that the value of image diagnose is not in the best condition.Objective: Holding device can clog the anus so that the contrast media is not to come out of the intestine during the examination. The population in this study is the patients who perform the examination of colon in loop at age above 50 years. Contrast media holding tool is expected to help the process of examination of colon in loop for maximum radiograph results so as to get the best diagnosis.Method: The type of research is explorative experimental research by making contrast media holding tool at the examination of colon in loop. Data collection method used is by filling sheets of questionnaires in the form of check list by the respondents in the hospital Radiology Installation concerned. The data collected and performed data processing and presented in the form of percentage so that it can be taken conclusions and suggestions.Result: Contrast media holding tool on Colon in Loop examination with patient over 50 years old can prevent contrast media to reflukss. Based on the calculation of recapitulation of questionnaire results on 10 respondents in Radiology Installation RSI Sultan Agung and RSUD Pandan Arang Boyolali, get the percentage of 94%.Conclusion: Based on the percentage of questionnaire results, it can be concluded that the tool is very feasible to use and able to hold the contrast media.